Optical time division multiplexing for optical communication system - Ngah, Razali (Faculty of Electrical Engineering, 2008)
Fibre nonlinearities are limiting factors for optical communications systems, in particular for wavelength division multiplexing (WDM). Among the nonlinearities effect is four wave mixing (FWM), which is a nonlinear process that generates new frequency components from existing frequency components. FWM is the main factor which ultimately limits the channel density and capacity of WDM systems. Many studies have been carried out on the fiber nonlinear effects in WDM baseband-optical modulated systems but very few have been published on radio-over-fiber (ROF)-WDM system. Therefore, this research has put a core situation in studying the FWM effect in ROF-WDM systems which carry the modulated microwave carrier and baseband signal. In the ROF-WDM system, the optical modulation technique plays a vital role in amount of fiber nonlinearity effect. Therefore, in this regards, different types of ROF-WDM system in terms of optical modulation techniques are investigated and the drawback and advantages of these techniques are compared. Among these modulated technique, the most suspected optical modulation technique to fiber nonlinearity which is direct intensity modulation is chosen to be modeled for the ROF-WDM system. The model of the WDM baseband optical modulated system is initially developed to investigate the effect of FWM. In this way, the FWM in conventional WDM system is firstly investigated. By using this model fiber nonlinearity effects in conventional optical system is observed and some effects of fiber nonlinearity by changing the parameters such as channel spacing and the power level are verified. After doing this procedure, a computer model of ROF-WDM system is developed to analyze the FWM effect in the system. In this regards a ROF-WDM system that uses 30 GHz millimeter wave signal to carry the baseband data rate of 2.5 Gb/s is modeled. The results have shown that, in terms of generating FWM component, ROF-WDM system with double sideband transmission is more productive. Therefore, the FWM effect is more destructive than baseband modulation optical system. However, single sideband transmission in ROF can alleviate the FWM impact in certain level. Finally, at the end of the project, some possible solutions and suggestions to mitigate the FWM effect in ROF-WDM system are proposed.